2021
DOI: 10.3390/plants10122751
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhiza glabra (Licorice): A Comprehensive Review on Its Phytochemistry, Biological Activities, Clinical Evidence and Toxicology

Abstract: There are more than 30 species of Glycyrrhiza genus extensively spread worldwide. It was the most prescribed herb in Ancient Egyptian, Roman, Greek, East China, and the West from the Former Han era. There are various beneficial effects of licorice root extracts, such as treating throat infections, tuberculosis, respiratory, liver diseases, antibacterial, anti-inflammatory, and immunodeficiency. On the other hand, traditional medicines are getting the attraction to treat many diseases. Therefore, it is vital to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
42

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 221 publications
0
70
0
42
Order By: Relevance
“…Over 50% of all pharmaceutical drugs are still natural ingredients [ 129 , 130 ]. Currently, natural sources such as plants, microorganisms, and sea creatures account for more than 60% of commercially accessible anticancer medicines [ 131 , 132 , 133 , 134 ]. A total of 3000 plant species have been utilized to treat various kinds of cancer [ 132 , 135 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Over 50% of all pharmaceutical drugs are still natural ingredients [ 129 , 130 ]. Currently, natural sources such as plants, microorganisms, and sea creatures account for more than 60% of commercially accessible anticancer medicines [ 131 , 132 , 133 , 134 ]. A total of 3000 plant species have been utilized to treat various kinds of cancer [ 132 , 135 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Enoxolone is a pentacyclic triterpenoid aglycone metabolite of glycyrrhizin that is found in licorice. It exhibits a range of pharmacological properties including antitumor, anti-inflammatory, and anti-viral activities (22). We decided to focus on enoxolone due its greater potency, chemical tractability, and reports of related pentacyclic triterpenoids that show anti-virulence against various bacteria (23).…”
Section: Resultsmentioning
confidence: 99%
“…From screening of structurally diverse phytochemicals, we identified that the triterpenoid enoxolone (18β-glycyrrhetinic acid) inhibits toxin biosynthesis by perturbing multiple metabolic pathways in C. difficile . Enoxolone is an aglycone metabolite of glycyrrhizin, the main bioactive component of licorice root extracts ( Glycyrrhiza [sweet root]) (22). Licorice has a long history of use as a traditional Chinese medicine and is widely consumed in dietary supplements, herbal tea, confectionaries, beverages and cosmetics in the USA, Middle East, Asia, and Europe (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquorice (Glycyrrhizae radix et rhizome), the roots of Glycyrrhiza uralensis Fisch., Glycyrrhiza glabra L. or Glycyrrhiza inflate Bat., has long been used as a tonic herbal medicine in traditional Chinese medicine (TCM) due to its ability to harmonize unpleasant characteristics of other herbs or reduce the toxicities of certain herbs when used together in the herbal formulas ( Wang et al, 2013 ; Wahab et al, 2021 ). In China, although there are no reports on the scientific rationale, liquorice is presented with PA-containing herbs in TCM compound formulas, yet no PA-poisoning cases have been reported with this combinational use.…”
Section: Introductionmentioning
confidence: 99%